Aspek Gizi dan Fungsional Tepung Bawang Dayak (Eleutherine palmifolia (L) Merr) : Kajian Pengeringan Menggunakan Fluid Bed dan Cabinet Dryer - Erawati, Christina Mumpuni; Retanubun, Adeola Angela; Pantjajani, Tjandra (HB PRESS, 2024)
Dayak onion is a type of medicinal plant that grows in several areas and has been used for generations to cure various diseases in Kalimantan, Indonesia. Dayak onion contains bioactive compounds such as phenolic, flavonoids, saponins, tannins and naphtoquinones which can act as antioxidants, anti-microbials, and anti-inflammatories. Currently the application of Dayak onions is still rare even though it has many benefits. This study aims to characterize nutritional and functional aspects of dayak onion flour with various drying temperature using fluidized bed dan cabinet dryer. The research design used is factorial design. The characterization of Dayak onion flour carried out was yield, moisture content, ash, protein, fat, concentration of IC50, WHC and OHC. Microbial contamination tests carried out included ALT, E.coli, and mold. In the research results, the best nutrition and functional aspect of Dayak onion flour was drying with temperature 40? in the cabinet and fluidized bed dryer. Determination of the best results is taken based on the De Garmo test where the two samples have the highest value of effectiveness in each method. The best concentration of IC50 is Dayak onion flour using the cabinet dryer with a temperature of 35? that was 3703,43 ppm. In addition, no growth of E.coli and mold bacteria was found and the number of bacterial colonies was still classified as safe when compared to the SNI for cassava flour so that dayak onion flour was safe against microbial contamination.